A Middle Pleistocene Northeast Atlantic coccolithophore record: paleoclimatology and paleoproductivity aspects - Amore, F. O.; Flores, José Abel; Voelker, A. H. L.; Martín Lebreiro, Susana; Palumbo, E.; Sierro, Francisco J. (Marine Micropaleontology, 2020)
Changes in paleoclimate and paleoproductivity patterns have been identified by analysing, in conjunction with other available proxy data, the coccolithophore assemblages from core MD03-2699, located in the Portuguese margin in the time interval from the Marine Isotope Stage (MIS) 13/14 boundary to MIS 9 (535 to 300 ka). During the Mid-Brunhes event, the assemblages associated with the eccentricity minima are characterised by higher nannoplankton accumulation rate (NAR) values and by the blooming of the opportunistic genus Gephyrocapsa. Changes in coccolithophore abundance are also related to glacial–interglacial cycles. Higher NAR and numbers of coccoliths/g mainly occurred during the interglacial periods, while these values decreased during the glacial periods. Superimposed on the glacial/interglacial cycles, climatic and paleoceanographic variability has been observed on precessional timescales. The structure of the assemblages highlights the prevailing long-term influence of the Portugal (PC) and Iberian Poleward (IPC) Currents, following half and full precession harmonics, related to the migration of the Azores High (AH) Pressure System. Small Gephyrocapsa and Coccolithus pelagicus braarudii are regarded as good indicators for periods of prevailing PC influence. Gephyrocapsa caribbeanica, Syracosphaera spp., Rhabdosphaera spp. and Umbilicosphaera sibogae denote periods of IPC influence. Our data also highlights the increased percentages of Coccolithus pelagicus pelagicus during the occurrence of episodes of very cold and low salinity surface water, probably related to abrupt climatic events and millennial-scale oscillations of the AH/Icelandic Low (IL) System Dipartimento di Scienze e Tecnologie, Università del Sannio, Italia Departamento de Geología, Universidad de Salamanca, España Unidade de Geologia Marinha, Laboratório Nacional de Energia e Geologia, Portugal Centro Interdisciplinar de Investigação Marinha e Ambiental Associated Laboratory, Portugal Instituto Geológico y Minero de España, ...